2008
DOI: 10.1111/j.1479-8301.2008.00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating early and late‐onset depression with multichannel near‐infrared spectroscopy

Abstract: Background: Individuals with late-life depression can be divided into two categories, those with early and late-onset depression (EOD and LOD, respectively). It has been reported that LOD has more accentuated subcortical vascular lesions and frontal lobe dysfunction (hypofrontality). The aim of the present study was to examine whether LOD exhibits more prominent hypofrontality than EOD during performance of the word fluency task (WFT) under multichannel near-infrared spectroscopy (NIRS), a newly developed non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The NIRS instruments that were used varied markedly across studies. One study used single‐channel NIRS (HEO‐200, Omron, Tokyo, Japan), one study used two‐channel NIRS (NIRO‐300, Hamamatsu Photonics K.K., Hamamatsu City, Japan), two studies used 24‐channel NIRS (Hitachi ETG‐100, Hitachi Medical Corporation, Tokyo, Japan), one study used 28‐channel CW5 NIRS (TechEn, Milford, MA, USA), and nine studies used 52‐channel NIRS (Hitachi ETG‐4000) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NIRS instruments that were used varied markedly across studies. One study used single‐channel NIRS (HEO‐200, Omron, Tokyo, Japan), one study used two‐channel NIRS (NIRO‐300, Hamamatsu Photonics K.K., Hamamatsu City, Japan), two studies used 24‐channel NIRS (Hitachi ETG‐100, Hitachi Medical Corporation, Tokyo, Japan), one study used 28‐channel CW5 NIRS (TechEn, Milford, MA, USA), and nine studies used 52‐channel NIRS (Hitachi ETG‐4000) …”
Section: Resultsmentioning
confidence: 99%
“…Studies included in quantitative synthesis of deoxyHb (n = 5) 22 one study used two-channel NIRS (NIRO-300, Hamamatsu Photonics K.K., Hamamatsu City, Japan), 23 two studies used 24-channel NIRS (Hitachi ETG-100, Hitachi Medical Corporation, Tokyo, Japan), 24,25 one study used 28-channel CW5 NIRS (TechEn, Milford, MA, USA), 25 and nine studies used 52-channel NIRS (Hitachi ETG-4000). [27][28][29][30][31][32][33][34][35] According to our review of the authors' conclusions, all of the studies reached the unanimous conclusion that patients with MDD had significantly lower activation of the prefrontal cortex during cognitive tasks than controls. However, for quantitative meta-analysis, the original data needed were incomplete or missing in most of the included studies.…”
Section: Study Characteristicsmentioning
confidence: 91%
See 1 more Smart Citation
“…The elderly depression is heterogeneous, requiring various interventions, [18][19][20] and different pathogenic processes are speculated with younger elderly and older elderly depression. 21,22 No study, however, has been reported the Ab levels in younger subjects with depression. The present study therefore examined serum Ab40 and Ab42 levels and the Ab40/42 ratio in patients with major depressive disorder (MDD) and healthy controls, and compared young and elderly groups.…”
Section: Introductionmentioning
confidence: 99%
“…Brain imaging techniques are very powerful in differentiating between Alzheimer's disease (AD) and other diseases; however, they are inconvenient as an initial step. For the diagnosis of depression, physiological examinations and brain imaging, namely near‐infrared spectroscopy, have been used 3,4 and convenient methods are always required for use in routine clinical practice. For example, the usefulness of the electroencephalogram (EEG) has been reported recently.…”
Section: Introductionmentioning
confidence: 99%